Strategi Penerapan PSAK 104 pada Transaksi Istishna: Menuju Laporan Keuangan yang Baik: Strategy for Implementing PSAK 104 in Istishna Transactions: Towards Good Financial Reports - Nurul Wahyu; Niluh Anik Sapitri (HISAB: Jurnal Akuntansi Lembaga Keuangan Syariah, 2026)
The implementation of good accounting standards, particularly PSAK 104, is crucial for preparing transparent and accurate financial statements in Indonesia. PSAK 104 regulates the recognition, measurement, and disclosure of revenue from istishna transactions, which are agreements for the purchase of goods that do not yet exist and will be produced. This research explores the impact of implementing PSAK 104 on the transparency of financial statements, as well as the challenges faced by companies in its implementation. The findings indicate that a deep understanding of accounting standards, support from information technology, and training for accounting personnel are key strategies to enhance reporting quality. This study aims to contribute to better accounting practices and promote business sustainability in Indonesia.